KONSEP PERPAJAKAN MENURUT ABU YUSUF - Muhammad Fauzan (HUMAN FALAH: Jurnal Studi Ekonomi dan Bisnis Islam, 2017)
Abu Yusuf was one of the scholars and thinkers of Islam's most successful period of Caliph Harun ar-Rashid, this can be seen from the progress of the country and welfare of the people in the time of Abu Yusuf both in terms of economic, social, political, security and defense of the country, and the development of science knowledge and technology. In terms of thinking jurists Abu Yusuf is an homage to ahl ar-ra'yu, Abu Yusuf tend to describe various thoughts by using analytical tools qiyas preceded by conducting in-depth study of the Qur'an, the hadith of the Prophet, Atsar Shalabi, as well as the practice of pious rulers. Rationale is to bring al-mashlahah al'ammah (the public good). This approach makes a variety of ideas to be relevant and more stable. In terms of the economy, especially taxation, Abu Yusuf many uses diligences as outlined in the book Al-Kharaj. This of course raises the question: how does the concept of taxation according to Abu Yusuf? To obtain the answer to that question, this study aimed at library research (library research) which is a descriptive analysis that describes the overall biography of Abu Yusuf and Abu Yusuf thinking in terms of the economy, especially in terms of the concept of taxation. Data about Abu Yusuf thinking in terms of the economy, especially in terms of taxation explore concepts in the book Al-Kharaj, works of scholars, researchers and historians who wrote about Abu Yusuf. While the data related to this study traced in the sources of primary and secondary as well as previous studies. After a successful data are collected, grouped, categorized and discard unnecessary data and data obtained will be analyzed carefully. Based on the analysis of the data found that the economic rationale Abu Yusuf is economic thought appropriate/suitable with the state of society at that time. In terms of the concept of taxation, which is the source of state revenue in the future of Abu Yusuf is kharaj, jizyah, usyur, alms, ghanimah and fa'i.